Effect of Grafting Nano-TiO2 on Sansevieria cylindrica Fiber Properties - Wiguna, Chrisrulita Sekaradi; Suryanto, Heru; Aminnudin, Aminnudin; Binoj, Joseph Selvi; Ali, Alamry (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
Natural fibers, which are abundant, environmentally friendly, and biodegradable, are used as a replacement for synthetic fibers. The composite strength can be increased by treating the surfaces of natural fibers with suitable chemicals, which can also improve the interface interaction between fiber and matrix. Application of a coupling agent in chemical treatment is utilized to reinforce the bonding between fiber and matrix. The objective of the study is to determine the influence of silane concentration on the Sansevieria cylindrica fiber properties. The methods included fibers treatment using ethanol and coupling agent as dissolving and TiO2 with concentrations of 0 percent, 0.25 percent, 0.5 percent, 0.75 percent, and 1 percent. The mechanical strength testing was conducted through a single fiber test. Fiber morphology was observed using an electron microscope. FTIR analyzes the change in fiber chemical composition caused by TiO2 addition. As a result, the morphology of S. cylindrica fibers became rougher and showed a rougher surface after a silane concentration of 1 percent, but with the proper concentration, some fiber surfaces provided a good interface. Ti-O bonds are formed at a wavelength of 475 cm-1. The shift in a peak at 400–500 cm-1 indicates Ti-O-Ti group stretching vibrations believed to have originated from TiO2 particles. The mechanical strength increases as the concentration of TiO2 increases, with the highest fiber strength of 284.66 MPa observed at a TiO2 concentration of 1 percent. This represents a 26 percent higher tensile strength compared to the control specimen.